2005
DOI: 10.1111/j.1525-1470.2005.22415.x
|View full text |Cite
|
Sign up to set email alerts
|

Unilateral Congenital Linear Atrophoderma of the Leg

Abstract: We report an infant with depressed, hypopigmented, linear plaques of congenital onset on the lower extremity. The lesions were asymptomatic and the child was otherwise healthy. Despite the clinically obvious change in skin texture and color, histopathologic changes were subtle: a biopsy specimen showed hypopigmentation and a decrease in elastic fibers in the papillary and upper reticular dermis. Diagnoses considered included various congenital syndromes, idiopathic atrophoderma of Pasini and Pierini, and espec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 19 publications
(29 reference statements)
0
20
0
2
Order By: Relevance
“…Review of the literature reveals two cases of congenital APP: a female case born with erythematous atrophic lesion on the right shoulder and a male case born with a plaque of APP on his lower right back . Ang et al . presented a child with congenital, linear, hypopigmented atrophoderma of the lower extremity, which shared some clinical features with ALM.…”
Section: Discussionmentioning
confidence: 99%
“…Review of the literature reveals two cases of congenital APP: a female case born with erythematous atrophic lesion on the right shoulder and a male case born with a plaque of APP on his lower right back . Ang et al . presented a child with congenital, linear, hypopigmented atrophoderma of the lower extremity, which shared some clinical features with ALM.…”
Section: Discussionmentioning
confidence: 99%
“…Hematoxylin and eosin staining usually shows hyperpigmentation only in basal epidermal layers without abnormal collagen or elastic fibers in the dermis or any obvious inflammation [1, 3, 4]. There may be some perivascular lymphocytic infiltration [2, 512], acanthosis [7, 8], epidermal atrophy [6], altered collagen in the dermis [2, 57, 9, 10, 13], and decreased or fragmented elastic tissue [14]. Once there is some alteration of the collagen component, the diagnosis should be atrophoderma of Pasini and Pierini (APP) [15].…”
Section: Discussionmentioning
confidence: 99%
“…Linear scleroderma and APP may show a segmental atrophic plaque similar to LAM. Abnormal collagen fibers in the histopathological findings and dermal tissue reduction in the ultrasound imaging are helpful for the diagnosis of linear scleroderma and APP, respectively [2, 14]. Considering the clinical manifestation of LAM, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These variants include bilateral telangiectatic lesions, the presence of leukonychia, lentiginous variant and neck localization. Ang et al [25] reported a case of unilateral congenital atrophoderma of the leg and discussed a congenital form of LAM, but lesions were hypopigmented and they observed a decrease in elastic fibers in the papillary dermis with elastin stains. In our view, only cases with clearly pigmented and atrophic lesions arranged along Blaschko's lines should be considered as LAM.…”
Section: Discussionmentioning
confidence: 99%